The influence of design character on logo recall / Muhamad Abdul Aziz Ab Gani - Ab Gani, Muhamad Abdul Aziz (2014)
Logo is an important part of branding aspect especially in creating an identity for the brand. The definition of a logo actually is virtually limitless and cannot be restrict in today's globalized and borderless world. The reason is the growth and evolution of logo design has made a logo being valued not only from the definition aspect, but going further as a medium for communication and conveying messages (Armstrong, 2009). Nevertheless, in theory, a logo must at least easy to be remembered and recognize, as mentioned by Klerkx & Meurs (2006) that a logo design must emphasize on the elements that are easily remembered by the audience and thus, the brand represented by the logo is more well-known than competitors. Once a brand is known, the products will have more sales potential. This, according to Haig & Harper (1997) depends on the role and function of a logo design, which is to be easily remembered. From the basic principle of a logo design that is to make it easy to be remembered, several important questions arises through a research process. The most important question is what is the most significant factor that makes a logo easy to be remembered. As the result, this research focused on design characters exist in a logo design which involve shape, line, colour, typography, and image in finding the most significant factor in making a logo easy to be remembered. There are three objectives outlined for this research. The first one is to explore the design characteristic of logos used in Peninsular Malaysia's SME companies and product. The second objective is to determine which of the design characteristic that are more easily recognize and remember. The final objective is to establish the design characteristic in the context Malaysia. This, to ensure the objectives of this research are achieved, the 'mix method' approach was applied and implemented during this research where qualitative approach was used to achieve the first objective while quantitative approach has helped to achieve the second and third objectives. Positively, the findings from the analysis shows that each of the design character (shape, line, colour, typography & image) used in a logo design is significant to our memorization. From the five design characters, typography is the most significant design character in terms of making a logo easy to be remembered. Finally, this research has a direct contribution in four main aspects. The first one is theoretical contributions where this research has collected various theories from different aspects and field related to design character. The second contribution is in the methodological aspects where this research has produced a new theoretical framework that can be used in future researches. Third, this research has a good practical contribution where it can be use by designer and decision maker as a guide in producing best logo design. Lastly, in the aspect of social contribution, this research can be benefited by the society in understanding the role and function of a logo in our daily lives.